Increase of photogenerated carriers in thick quantum wells in InGaN solar cells verified by laser-assisted capacitance-voltage measurement. (25th April 2017) - Liu, Wei; Zhao, Degang; Jiang, Desheng; Chen, Ping; Shi, Dongping; Liu, Zongshun; Zhu, Jianjun; Yang, Jing; Li, Xiang; Liang, Feng; Liu, Shuangtao; Xing, Yao; et al.
Abstract: For the InGaN/GaN multiple quantum well (MQW) solar cells, it is known that in the thicker InGaN QWs the collection of photogenerated carriers suffer from the impact of both stronger piezoelectric field and enhanced non-radiative recombination process, which may lead to an inferior performance for thick-well solar cells. However, we find that the photovoltaic intensities of our MQW solar cells with different well thickness are almost the same. Combined with the profiles of apparent carrier concentration obtained from the capacitance-voltage measurement with additional laser illumination, we conclude that the increase of photogenerated carriers in the thick QWs may partially counteract the adverse effects of both polarization effect and deteriorated material quality on the photocurrent for the MQW solar cells with thick InGaN well layers, compared with the thin-well ones.